Yeast Lsm1p-7p/Pat1p Deadenylation-Dependent mRNA-Decapping Factors Are Required for Brome Mosaic Virus Genomic RNA Translation - Noueiry, Amine O. (American Society for Microbiology, 2003)
Previously, we used the ability of the higher eukaryotic positive-strand RNA virus brome mosaic virus (BMV) to replicate in yeast to show that the yeast LSM1 gene is required for recruiting BMV RNA from translation to replication. Here we extend this observation to show that Lsm1p and other components of the Lsm1p-Lsm7p/Pat1p deadenylation-dependent mRNA decapping complex were also required for translating BMV RNAs. Inhibition of BMV RNA translation was selective, with no effect on general cellular translation. We show that viral genomic RNAs suitable for RNA replication were already distinguished from nonreplication templates at translation, well before RNA recruitment to replication. Among mRNA turnover pathways, only factors specific for deadenylated mRNA decapping were required for BMV RNA translation. Dependence on these factors was not only a consequence of the nonpolyadenylated nature of BMV RNAs but also involved the combined effects of the viral 5′ and 3′ noncoding regions and 2a polymerase open reading frame. High-resolution sucrose density gradient analysis showed that, while mutating factors in the Lsm1p-7p/Pat1p complex completely inhibited viral RNA translation, the levels of viral RNA associated with ribosomes were only slightly reduced in mutant yeast. This polysome association was further verified by using a conditional allele of essential translation initiation factor PRT1, which markedly decreased polysome association of viral genomic RNA in the presence or absence of an LSM7 mutation. Together, these results show that a defective Lsm1p-7p/Pat1p complex inhibits BMV RNA translation primarily by stalling or slowing the elongation of ribosomes along the viral open reading frame. Thus, factors in the Lsm1p-7p/Pat1p complex function not only in mRNA decapping but also in translation, and both translation and recruitment of BMV RNAs to viral RNA replication are regulated by a cell pathway that transfers mRNAs from translation to degradation.